Development of a Power Generator System Using Thermal Waste from a Car - Johari, Siti Halma; Ab Wahab, Norfariza; Abd. Mutalib, Nurliyana; Ahmad, Suziana; Abdul Hadi, Dayanasari; Zahari, Madiha; Hashim, Norlezah; Mazwin Mazlan, (International Journal of Integrated Engineering, 2019)
Wasted energy is created in our surroundings, including in a car’s operating system. This paper presents the development of a power generator system using thermal waste from a car. Energy cannot be created or destroyed but it can be transferred or changed into other forms. Therefore, the objectives of this project are to study a working principles of Peltier and DC-DC boost converter, to propose a new power generator system by reusing the wasted thermal and generate a stable electric to supply car devices. A power generator system is created to reuse the thermal wasted. The system uses a thermoelectric generator to convert heat energy from a car to electrical energy when a difference in temperature occurs. The conversion process is achieved by using a Peltier module. With the small amount of voltage produced from the process, a DC-DC boost converter is used to boost the voltage from the converted voltage. The result of this study, the desired output voltage produce 5 V and it useful to supply back for car’s devices or charge small electronic devices.